Development Of Education Comics Based Realistic Mathematics Education On Fraction Material - Lestari, Arika Celsie Puji; Ekawati, Rooselyna (Universitas Negeri Surabaya, 2019)
The research aims to describe the process and the result of the RME-based comics education on fraction material approach measured by aspects validity, practicality, and effectiveness. The subject of this research were students grade-7 junior high school. This research is development research with the five stages ADDIE model, and they are analysis, design, development, implementation, and evaluation. This research showed that RME-based comics education is valid, very practically, and effective.